2011
DOI: 10.1089/jmf.2010.1213
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Activity and Expression of Antioxidant Enzymes by Solvent Fractions and Isolated Compound from Cedrela sinensis Leaves in HepG2 Cells

Abstract: Cedrela sinensis has been widely used in traditional Oriental medicine to treat a variety of diseases. However, little is known about the cellular actions by which this plant mediates its antioxidant effects. In this study, activity-guided fractionations of C. sinensis leaves were performed using column chromatographic techniques as well as biological assays with HepG2 cells. The ethanol (95%) extract of C. sinensis leaves was sequentially extracted with hexane, chloroform, ethyl acetate (EtOAc), butanol, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Accordingly, numerous bioactive plant materials have been investigated for their antioxidant potential (4,(6)(7)(8). In the present study, to the best of our knowledge, we demonstrate for the first time that FBG protects HepG2 cells against H 2 O 2 -induced oxidative stress through the regulation of ROS production and antioxidant enzymes, and signaling pathways including MAPKs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Accordingly, numerous bioactive plant materials have been investigated for their antioxidant potential (4,(6)(7)(8). In the present study, to the best of our knowledge, we demonstrate for the first time that FBG protects HepG2 cells against H 2 O 2 -induced oxidative stress through the regulation of ROS production and antioxidant enzymes, and signaling pathways including MAPKs.…”
Section: Discussionsupporting
confidence: 51%
“…Phytochemicals provide further protection against oxidative damage from free radicals. A large number of studies have indicated that phytochemicals present in fruits, vegetables and herbs, exert their antioxidant effects against oxidative stress through the induction or activation of these endogenous antioxidant enzymes (6)(7)(8)(9). In addition, increased ROS production not only directly damages cells by oxidizing macromolecules, such as DNA and lipids, but also indirectly by triggering mitogen-activated protein kinase (MAPK) signaling pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been few reports on the effect of ginseng ingredients on the relationship between antioxidant enzymes and MAPKs pathways. Our previous study demonstrated that a flavonoid quercitrin from Cedrela sinensis down-regulates H 2 O 2 -induced phosphorylations of Akt and three MAPKs (ERK, JNK, and p38) in HepG2 cells [7]. In the study, we found that quercitrin-induced expression of GPx was ameliorated by the p38-specific inhibitor and the Akt/PI3K inhibitor, whereas the expression of SOD by quercitrin was diminished only by the p38 inhibitor.…”
Section: Resultsmentioning
confidence: 87%
“…The activity and expression of the antioxidant enzymes can be modulated by cellular proteins like mitogen-activated protein kinases (MAPKs) such as c-Jun N -terminal kinase (JNK), extracellular-regulated kinase (ERK), and p38, as well as the upstream kinases including phosphoinositide kinase-3 (PI3K)/Akt [6]. A variety of phytochemicals from fruits, vegetables and herbs have been studied for their ability to protect cells against oxidative stress via the induction or activation of antioxidant enzymes [710]. …”
Section: Introductionmentioning
confidence: 99%
“…T. sinensis leaves contain a variety of bioactive compounds such as gallic acid, methyl gallte, kaemferol, quercetin, rutin, quercitrin, palmitic acid and linoleic acid, etc. [ 9 , 10 , 11 , 12 ]. Of these compounds, quercitrin (3-rhamnosyl quercetin) ( Figure 1 ), a glycoside of quercetin, has been found as a main bioactive constituent in T. sinensis leaves [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%